Phase‐Only Tuning of Extreme Huygens Metasurfaces Enabled by Optical Anisotropy. Issue 2 (14th November 2021) - Yang, Ziwei; Liu, Mingkai; Komar, Andrei; Xu, Lei; Neshev, Dragomir N.
Abstract: Pure phase modulation of light is vital for a number of optical devices such as spatial light modulators and beam steering in light detection and ranging (LIDAR) technologies. Tunable metasurfaces have recently provided a feasible alternative to existing technologies, allowing for ultra‐high miniaturisation while enabling high transmission efficiency and tunability under small external stimuli. However, despite the recent advances in the field, no pure phase tuning has been demonstrated in transmissive devices, for example, any implementation of continuous phase tuning is accompanied by sizable amplitude modulation or low efficiency. Here, it is shown that the optical anisotropy of the surrounding material can enable phase‐only tuning of optical metasurfaces in the full 2π range with unitary efficiency over a sizable bandwidth. A practical implementation of this concept based on a liquid‐crystal infiltrated metasurface operating in the regime of extreme Huygens condition is further proposed. In this way, the full 2π phase‐only tunability in transmission can be enabled by controlling bias voltage and temperature variation of the surrounding liquid crystal. Abstract : Dynamically tunable metasurfaces offer important applications in compact high‐performance light detection and ranging (LIDAR) and dynamic holography. However, conventional tunable metasurfaces cannot achieve a continuous full 2π‐phase coverage or come at the expense of significant intensity modulation. This article provides a pure phase dynamic tuning method by exploring the optical anisotropy of the surrounding material of a metasurface to achieve 2π phase change with unity efficiency.